2010
DOI: 10.1108/10610421011046201
|View full text |Cite
|
Sign up to set email alerts
|

How budget constraints impact consumers' response to discount presentation formats

Abstract: Purpose -This research aims to study how buyers' budget constraints influence buyers' perceptions of discounts presented in a dollars-off versus percentage-off format. A comparison of perceptions of discount format under budget constraints is missing from the past literature. The current research aims to fill this gap. Design/methodology/approach -The research is based on two experiments. In the first experiment, a study by Kahneman and Tversky is replicated and extended by including budget constraints. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…According to the Mann-Whitney U test, the results show that ȥ=-5.40, p < 0.05; the second variant (M=37.04) has a lower score than the first variant (M=62.70). This finding was aligned with the prospect theory concept, that most individuals will accept the discount or price reduction at a high price (expensive) than at low price (cheap) (Scheer et al, 2010), even though the level of discount is only 33.3%. The results on the acceptance or rejection of the book discount are shown in Table 1.…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…According to the Mann-Whitney U test, the results show that ȥ=-5.40, p < 0.05; the second variant (M=37.04) has a lower score than the first variant (M=62.70). This finding was aligned with the prospect theory concept, that most individuals will accept the discount or price reduction at a high price (expensive) than at low price (cheap) (Scheer et al, 2010), even though the level of discount is only 33.3%. The results on the acceptance or rejection of the book discount are shown in Table 1.…”
Section: Resultssupporting
confidence: 76%
“…Kahneman and Tversky (1984) state that individuals will discover the result of their choice in losses or gains. Other research has also found that people will use their perception of promotions or discounts in terms of loss or gain to decide to purchase the product and that sellers use this to create several types of promotion (Diamond & Campbell, 1989;Kazmi, 2015;Scheer et al, 2010). Individuals will perceive gain if the purchase price (price promotion) is lower than the reference price; otherwise, when the purchase price is higher than the reference price, they will perceive loss (Crompton, 2016).…”
Section: Mental Budgeting and The Malleability Of Decision Makingmentioning
confidence: 99%
See 3 more Smart Citations